Children's propensity to consume sugar and fat predicts regular alcohol consumption in adolescence. Issue 17 (24th August 2018) - Mehlig, Kirsten; Bogl, Leonie H; Hunsberger, Monica; Ahrens, Wolfgang; De Henauw, Stefaan; Iguacel, Isabel; Jilani, Hannah; Molnár, Dénes; Pala, Valeria; Russo, Paola; Tornaritis, Michael; Veidebaum, Toomas; et al.
Abstract: Objective: The present study investigated the association between sugar and fat intake in childhood in relation to alcohol use in adolescence. We hypothesized that early exposure to diets high in fat and sugar may affect ingestive behaviours later in life, including alcohol use. Design/Setting/Subjects: Children from the European IDEFICS/I.Family cohort study were examined at ages 5–9 years and followed up at ages 11–16 years. FFQ were completed by parents on behalf of children, and later by adolescents themselves. Complete data were available in 2263 participants. Children's propensities to consume foods high in fat and sugar were calculated and dichotomized at median values. Adolescents' use of alcohol was classified as at least weekly v . less frequent use. Log-binomial regression linked sugar and fat consumption in childhood to risk of alcohol use in adolescence, adjusted for relevant covariates. Results: Five per cent of adolescents reported weekly alcohol consumption. Children with high propensity to consume sugar and fat were at greater risk of later alcohol use, compared with children with low fat and low sugar propensity (relative risk=2·46; 95 % CI 1·47, 4·12), independent of age, sex and survey country. The association was not explained by parental income and education, strict parenting style or child's health-related quality of life and was only partly mediated by sustained consumption of sugar and fat into adolescence. Conclusions: Frequent consumption of foods high in fat and sugar in childhood predicted regular use of alcohol in adolescence.